2020
DOI: 10.1186/s13045-020-00936-9
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalks between inflammasome and autophagy in cancer

Abstract: Both inflammasomes and autophagy have important roles in the intracellular homeostasis, inflammation, and pathology; the dysregulation of these processes is often associated with the pathogenesis of numerous cancers. In addition, they can crosstalk with each other in multifaceted ways to influence various physiological and pathological responses, including cancer. Multiple molecular mechanisms connect the autophagy pathway to inflammasome activation and, through this, may influence the outcome of pro-tumor or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 152 publications
(215 reference statements)
0
60
0
Order By: Relevance
“…Autophagy: Autophagy, an intracellular lysosomal degradation pathway, is classified into canonical and noncanonical autophagy pathways. [189][190][191][192] Recent studies have shown that numerous autophagy receptors containing ubiquitin-binding domains and LC3-interacting regions are involved in selective autophagy pathways targeting various types of cargo, including mitochondria, macromolecules such as lipids, aggregated proteins, and intracytoplasmic microbes. 193 In addition, LC3-associated phagocytosis (LAP) targets phagocytosed particles, such as dying cells or extracellular pathogens.…”
Section: Dual Regulatory Mechanisms Controlling the Nlrp3 Inflammasomementioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy: Autophagy, an intracellular lysosomal degradation pathway, is classified into canonical and noncanonical autophagy pathways. [189][190][191][192] Recent studies have shown that numerous autophagy receptors containing ubiquitin-binding domains and LC3-interacting regions are involved in selective autophagy pathways targeting various types of cargo, including mitochondria, macromolecules such as lipids, aggregated proteins, and intracytoplasmic microbes. 193 In addition, LC3-associated phagocytosis (LAP) targets phagocytosed particles, such as dying cells or extracellular pathogens.…”
Section: Dual Regulatory Mechanisms Controlling the Nlrp3 Inflammasomementioning
confidence: 99%
“…[193][194][195][196] Autophagy acts as the principal inhibitory pathway to limit excessive activation of the NLRP3 inflammasome in the context of various pathological conditions. [189][190][191][192] As numerous reviews have summarized the relationship between autophagy and the inflammasome, [189][190][191][192]197,198 in this section, we describe recent work regarding the mechanisms by which autophagy pathways, in particular autophagy-related genes (ATGs), regulate NLRP3 inflammasome activation and its physiopathological consequences.…”
Section: Dual Regulatory Mechanisms Controlling the Nlrp3 Inflammasomementioning
confidence: 99%
“…Reactive Oxygen Species (ROS)], it promotes the elimination of oncogenic proteins, and stimulates the induction of the immune response in response to cellular stress (273). Additionally, it has been shown that autophagy could promote senescence in tumor cells in response to oncogenic stress, which results in decreased tumor growth (274,275).…”
Section: Role Of Autophagy In Vascular Remodeling In Cancermentioning
confidence: 99%
“…Sequestosome 1 (SQSTM1/p62) could severe as a signaling hub which interacts with LC3, and is degraded by autophagy (18). In addition, p62 overexpression has been proposed to increase selective autophagy through modulating ubiquitin signaling (19), Caveolin-1 (Cav1) is a scaffolding protein of caveolae on the plasma membrane that has been shown to be closely associated with oncogenesis and malignancy development. Elevated expression of Cav1 has been confirmed to promote the proliferation, differentiation and migration of cells of various cancers, such as lung, pancreatic, and breast cancers (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%